The Role of the Qur'anic Tahfidz Program in Building Students' Discipline and Responsibility: A Parent's Perspective at SDI Al-Hadiriyah Jakarta - Indriani Oktaviana Sugandi; Abd Hadi; Zainal Arifin (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2026)
Character education remains a cornerstone of Islamic elementary schooling in Indonesia, yet the majority of research on Qur'anic memorization (tahfidz) programs focuses on school-based outcomes while largely overlooking parents' observations of their children's character development at home. This qualitative descriptive study addresses that gap by examining a parent's perspective on how the tahfidz program at SDI Al-Hadiriyah Jakarta shapes students' discipline and responsibility. Data were gathered through in-depth semi-structured interviews with parents, triangulated with information from the school principal, tahfidz teacher, homeroom teacher, and a student. Purposive sampling was applied, and data were analyzed using the Miles and Huberman model (data reduction, display, and conclusion drawing). Findings reveal four major themes: (1) observable improvements in children's discipline in worship and study routines at home; (2) growth of responsibility and independence in managing memorization tasks; (3) significant individual variation shaped by children's personality and the intensity of parental support; and (4) both supporting factors (parental involvement, religious home environment) and constraining factors (gadget distraction, inconsistent parent engagement) influencing program outcomes. These findings highlight the indispensable role of school-family collaboration in maximizing the long-term impact of tahfidz programs on Islamic character formation.